Combination of ultracentrifugation and solid‐phase extraction with subsequent chromatographic analysis of α‐tocopherol in erythrocyte membranes. Issue 4 (2nd January 2015) - Plíšek, Jiří; Pospíchalová, Naďa; Khalikova, Maria; Aufartová, Jana; Solichová, Dagmar; Krčmová, Lenka Kujovská; Solich, Petr
<x xml:space="preserve">Abstract</x> A novel and rapid sample pretreatment technique based on a combination of ultracentrifugation and solid‐phase extraction for the determination of α‐tocopherol in human erythrocyte membranes by high‐performance liquid chromatography with ultraviolet detection is presented in this work. Red blood cell samples were ultracentrifuged (288 000 × g, 3 min, 4°C) in the presence of d‐mannitol, 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid and calcium chloride. The α‐tocopherol was then extracted from the erythrocyte membranes by solid‐phase extraction with n‐hexane in the presence of ascorbic acid. Tocopherol acetate was used as the internal standard. The extract was dissolved in methanol and separated on the monolithic column Chromolith Performance RP‐18e (100 × 4.6 mm) using 100% methanol as the mobile phase. The absorbance of α‐tocopherol was measured at a wavelength of 295 nm. The method was validated and showed sufficient accuracy and precision, ranging from 96.4 to 100.8% and from 4.5 to 6.3%, respectively. Moreover, the developed method was applied to the determination of erythrocyte α‐tocopherol in real samples from patients. The combined ultracentrifugation and solid‐phase extraction technique substantially decreased the time for the sample pretreatment step compared to liquid–liquid extraction and could be applicable for the quantitation of other analytes in erythrocyte membranes.